Assessment and Enhancement of Management Practices in Financial Enterprises - Beriso-Sotto, Marie Rose (Journal of Organizational and Human Resource Development Strategies, 2024)
The study provides a sound review of the management practices of financial enterprises, identified challenges encountered, and proposes a novel framework to equip financial enterprises to navigate future crises in. Descriptive correlation methodology was used with a validated questionnaire as the main data gathering tool. Results have shown that financial enterprises have been operating for seven years and above; offering loans as the major type of service offered; and, having seven and above employees utilizing computers in day by day transactions. A high extent of practice was perceived along customer focus and retention, followed by risk management, human resources, and operation strategies. Internal and external challenges encountered were focused on customer focus and retention, human resources, operation strategies, and least on risk management. Generally, there is no significant relationship between the management practices and internal and external challenges encountered except for external risk management. It was concluded that the financial enterprises are highly established and has a long exposure to management practices. Furthermore, financial enterprises are challenged with external risk management practices.